Optimizing labor duration with pilates: evidence from a systematic review and meta-analysis of randomized controlled trials - Arezoo Haseli; Farideh Eghdampour; Hosna Zarei; Zahra Karimian; Dara Rasoal (BMC, 2024)
Abstract Background Pilates has captured interest due to its possible advantages during pregnancy and childbirth. Although research indicates that Pilates may reduce labor duration, alleviate pain, and improve satisfaction with the childbirth experience, consensus on these outcomes remains elusive, underscoring the necessity for additional studies. Aim This systematic review and meta-analysis aimed to assess the impact of Pilates exercises on labor duration among pregnant women. Methods The online database was searched to yield the literature using the terms of 'Pilates', 'childbirth', and 'labor duration', and similar terms including PubMed, Clinical Key, Scopus, Web of Science, Embase, and Cochrane Database of Systematic Reviews up to June 25, 2023. Studies were considered eligible if they were randomized or clinical controlled trials (RCTs/CCTs) published in English, focusing on healthy pregnant women without exercise contraindications. The studies needed to include interventions involving Pilates or exercise movement techniques, a comparison group with no exercise, and outcomes related to labor duration, the period of the active phase, and the second stage of delivery. Results Eleven studies, totalling 1239 participants, were included in the analysis. These studies provided high-quality evidence from exercise only RCTs/CCTs. The findings indicated a significant reduction in the active phase of labor (8 RCTs, n = 1195; Mean Difference [MD] = -56.35, 95% Confidence Interval [CI] [-89.46 to -23.25]) and overall labor duration (8 RCTs, n = 898; MD = -93.93, 95% CI [-138.34 to -49.51]) in pregnant women who engaged in Pilates exercises compared to those who did not but doesn't affect on the duration of the second stage of labor (7 RCTs, n = 1135; MD = -0.11, 95% CI [-7.21 to 6.99]). Conclusions While this review primarily addresses the effects of Pilates on healthy and low-risk pregnant women, the findings suggest a potential role for Pilates in shortening labor duration. Therefore, engaging in Pilates or similar physical activities is recommended for pregnant women to potentially facilitate a more efficient labor process.